The normal mode analysis of the V2-TLR-9 docked complex. - Rehana Parvin (841451) (2025)
The illustration depicted (A) the domain motion of the docked 3D structure, (B) the co-variance map, (C) the elastic network, (D) the eigenvalue, and (E) the variance.